The Okur-Chung Neurodevelopmental Syndrome Mutation CK2K198R Leads to a Rewiring of Kinase Specificity - Caefer, Danielle M.; Phan, Nhat Q.; Liddle, Jennifer C.; Balsbaugh, Jeremy L.; O’Shea, Joseph P.; Tzingounis, Anastasios V.; Schwartz, Daniel (Frontiers in Molecular Biosciences, 2022)
Okur-Chung Neurodevelopmental Syndrome (OCNDS) is caused by heterozygous mutations to the CSNK2A1 gene, which encodes the alpha subunit of casein kinase II (CK2). The most frequently occurring mutation is lysine 198 to arginine (K198R). To investigate the impact of this mutation, we first generated a high-resolution phosphorylation motif of CK2WT, including the first characterization of specificity for tyrosine phosphorylation activity. A second high resolution motif representing CK2K198R substrate specificity was also generated. Here we report the impact of the OCNDS associated CK2K198R mutation. Contrary to prior speculation, the mutation does not result in a loss of function, but rather shifts the substrate specificity of the kinase. Broadly speaking the mutation leads to 1) a decreased preference for acidic residues in the +1 position, 2) a decreased preference for threonine phosphorylation, 3) an increased preference for tyrosine phosphorylation, and 4) an alteration of the tyrosine phosphorylation specificity motif. To further investigate the result of this mutation we have developed a probability-based scoring method, allowing us to predict shifts in phosphorylation in the K198R mutant relative to the wild type kinase. As an initial step we have applied the methodology to the set of axonally localized ion channels in an effort to uncover potential alterations of the phosphoproteome associated with the OCNDS disease condition.